Post-Islamism And Reform Islamic Law: The Challenges And Future Of Political Islam In Indonesia - Qodir, Zuly (AHKAM : Jurnal Ilmu Syariah, 2023)
In  Indonesian  politics,  post-Islamism  has  emerged  in  response  to the  rise  of  political  Islam  since  the  beginning  of  Reformasi  in  1998.  Post- Islamism is negotiable and accommodative, seeking to adapt to the Indonesian Archipelago’s political realities and actual social conditions. As such, it does not  promote  confrontation  with  political  powers—something  common  in the  Islamist  movements  that  gained  traction  before  Reformasi—even  as  it seeks to counteract the Islamist tendencies that have gained prominence  in contemporary Indonesia. This article finds that post-Islamism offers a future in which the political rights of all citizens are guaranteed while social justice and human rights are upheld. Post-Islamists promote neither the formalization of  sharia  law  nor  the  fundamental  transformation  of  the  Indonesian  state, but rather a substantive political ideology that welcomes (rather than rejects) democracy. Meanwhile, Islamic law in Indonesia includes sharia laws passed at  the  provincial  and  regency  levels  by  the  governor  or  regent  (Bupati) with political parties and traders. Although efforts to cultivate post-Islamist mindsets have been hindered by intolerant, exclusive, and extremist elements of Indonesian society, it is hoped that organizations such as Muhammadiyah and  Nahdlatul  Ulama  can  continue  to  maintain  a  moderate,  inclusive  and tolerant understanding of Islam.  Dalam  politik  Indonesia,  post-Islamisme  telah  muncul  sebagai tanggapan  terhadap  kebangkitan  Islam  politik  sejak  awal  Reformasi  tahun 1998. Post-Islamisme bersifat negosiatif dan akomodatif, berusaha beradaptasi dengan realitas politik dan kondisi sosial aktual di Indonesia. Dengan demikian, gerakan ini tidak mendorong konfrontasi dengan kekuatan politik, seperti yang umum  terjadi  pada  gerakan  Islamis  yang  mendapatkan  daya  tarik  sebelum Reformasi, bahkan ketika gerakan ini berusaha untuk melawan kecenderungan Islamis yang telah menjadi terkenal di Indonesia saat ini. Temuan artikel ini adalah bahwa Post-Islamisme menawarkan masa depan di mana hak-hak politik semua warga negara dijamin, keadilan sosial ditegakkan, dan hak asasi manusia dijunjung  tinggi.  Kaum  post-Islamis  tidak  mendukung  formalisasi  hukum syariah atau transformasi fundamental negara Indonesia, melainkan ideologi politik substantif yang menyambut (dan bukan menolak) demokrasi. Hukum Islam di Indonesia bermanifestasi dalam Perda Syariah Provinsi dan Kabupaten yang  disahkan  oleh  politisi  lokal  dan  gubernur  atau  bupati  yang  didukung partai  politik  dan  pedagang.  Meskipun  upaya  untuk  mengembangkan  pola pikir pasca-Islamisme telah terhalang oleh elemen-elemen masyarakat Indonesia yang  intoleran,  eksklusif,  dan  ekstremis,  diharapkan  organisasi-organisasi seperti Muhammadiyah dan Nahdlatul Ulama dapat terus mempertahankan pemahaman Islam yang moderat, inklusif, dan toleran.